Therapeutic role of melatonin in migraine prophylaxis: A systematic review. Issue 3 (January 2019) - Long, Rujin; Zhu, Yousheng; Zhou, Shusheng
Abstract: Background: Melatonin is the "clock factor" generated from pineal gland dominating regular circadian rhythm in humans. Migraine is one of the most severe and debilitating primary headache disorders. Thus far, many diseases have been found to associate with melatonin, including the migraine. Therefore, melatonin's therapeutic potential for migraine is drawing attention. Objectives: The aim of this study is to offer a systematic review of extant data of melatonin in migraine prophylaxis and to provide clinical implications and specific recommendations for future studies. Data sources and study methods: A systematic research was conducted in September 2018 by using PubMed and Google Scholar databases to search for science literature published after 1988. Results: In all, 7 eligible articles were identified, including 4 randomized controlled studies and 3 observational studies. Due to high heterogeneities and limited number of studies, meta-analysis was not feasible, and only systematic review was performed. The results show that present evidence cannot claim melatonin's effectiveness according to the conflicting outcomes; however, the two negative outcomes of melatonin not different from placebo and melatonin inferior to amitriptyline are possible under-powering because of methodological, pharmacological, and therapeutic shortcomings. Observational studies also support melatonin's efficacy in migraine. As a result, melatonin is very likely to benefit migraine in prophylaxis and may have a similar effectiveness to other main preventive medications. Immediate-release melatonin 3 mg was established as effective, melatonin receptor agonist (Agomelatine) 25 mg and prolonged-release melatonin 4 mg were observed efficacious in observational studies. Melatonin displayed ineffective in the 2-month trial; thus, 3 months or more may be an enough duration for migraine therapy. Despite melatonin being generally safe, emerging literature is illustrating that a few severe adverse effects can be caused by melatonin, for example, liver injuries, reproductive system dysfunctions, and detrimental immunostimulation. Conclusions: Melatonin is very likely to be a promising alternative for migraine prophylaxis. Current literature examining melatonin's efficacy in migraine prevention is growing, but still limited. Future studies of perfect design in methodology, pharmacology, and therapeutics are needed to achieve a deeper awareness of melatonin's role in migraine as well as more studies to explore the safety issues of melatonin medicine.